Correlation Between Reselection Rule Main Diagnosis and Accuracy Code - Linda Widyaningrum; Lutviana Devi (LPPM Universitas Duta Bangsa Surakarta, 2019)
The diagnosis code has a very important role in making policies for health care providers. This study is an analytical study with a cross sectional approach. The method used is observation, interview and check list. The study sample was 81 out of 431 inpatient medical record documents. and sampling technique with systematic random sampling from. Data analysis uses univariate and bivariate with Fisher's. The percentage of accuracy of reselection rules shows 64% accuracy (52 documents) and inaccurate is 36% (29 documents). The percentage of accuracy of reselection rules is 69 documents with a percentage of 85% and 12 documents incorrect with a percentage of 15%. The results of the Fisher's statistical calculation show no corelation to the primary diagnosis based on reselection rules with the accuracy of the diagnosis code based on ICD-10 (p = 0.529).